Development of innovation strategies for sports education - Devecioglu, Sebahattin; Sahan, Hasan; Tekin, Murat; Yildiz, Mustafa (Elsevier Science Bv, 2012)
Innovation is a driver of growth and well-being. New technologies, products, services and organizations create jobs and rejuvenate industries. This also presents new opportunities for innovation and improvement in education systems. Students are the futures of school education develop in students' awareness of innovation and innovation capability has a special status and role of the education activity course is an important way to achieve innovation. For some people the future for physical education is a future directed towards young people's future health and well-being and, more specifically, their current and future participation in physical activity and sport. Today, good physical education, Health Education is the top priority, and safety education of students is a top priority. Every beginning teacher in class, take advantage of the regular class safety education for students. Dress must be sportswear, sports shoes, which cannot bring with accessories, so as not to cause injury in sports, the teaching process to comply with classroom discipline, attention to the management of sports equipment, not chasing, in practice prior to observe the surrounding environment, safety first. Second, the warming part of the activities of the use and operation of multimedia design reflects the innovative with the development of technology, tape recorders, Computer speakers, wireless microphones and other Technology has greatly enhanced the use of means of classroom efficiency and enhance the classroom results. In this paper have describes of innovation strategies for sports education in the future
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: Innovation; Education; Strategy; Sports